These Granite Islands : A Novel - Stonich, Sarah, 1958- (Book collections on Project MUSE., 2001)
These Granite Islands is an arresting novel about a woman who, on her deathbed, recalls the haunting and fateful summer of 1936, a summer that forever changed her life. Sarah Stonich's debut novel, set on the Iron Range of Minnesota, is an intimate and gripping story of friendship, a portrait of marriage, and a meditation on the tragedy of loss.